Pengaruh Fluktuasi Harga Lada terhadap Tingkat Pengeluaran Biaya Konsumsi Rumah Tangga Petani di Desa Koronua Kecamatan Sabulakoa Kabupaten Konawe Selatan - Husni Husni; Syamsinar Syamsinar (Fakultas Pertanian Universitas Muhammadiyah kendari, 2022)
This research was conducted in Koronua Village, Sabulakoa District, South Konawe Regency from August to September 2021. The purpose of this study was to find out how the fluctuations in pepper prices were and to determine the effect of pepper price fluctuations on the level of family household consumption expenditure in Koronua Village, Sabulakoa District, South Konawe Regency. . The data analysis technique used in this research is descriptive qualitative and quantitative analysis. The results of this study indicate that the level of pepper price fluctuations in Koronua Village has decreased and varied price fluctuations but is within reasonable limits. Meanwhile, pepper price fluctuations have no significant effect on household consumption expenditures for each harvest in Koronua Village, with an average level of expenses. household consumption per month is Rp. 644,853, and the average consumption cost per harvest is Rp. 82,710.52 with a significance value of 0.420, this makes the consumption expenditure variable have no significant effect on price fluctuations because sig 0.420 > 0.05.